KINERJA DAN HARGA SAHAM PERUSAHAAN MANUFAKTUR PADA MASA PANDEMI COVID-19 - Marcellino, Calvin; Fitri, Yulia (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This research aims to simultaneously and partially examine the influence of profitability, liquidity, and solvency on stock prices in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange during the Covid-19 pandemic. This quantitative research uses secondary data sources through annual financial reports available on the official website of the Indonesia Stock Exchange and analyzed using a multiple linear regression model via SPSS version 23. The research population is manufacturing companies in the consumer goods industry sector using a purposive sampling technique of 61 companies. The criteria set are that manufacturing companies in the consumer industry sector submit annual financial reports in 2020 and 2021. The research results show that profitability, liquidity, and solvency variables simultaneously influence stock prices in manufacturing companies in the consumer goods industry sector. Then partially, liquidity and solvency do not affect stock price, but profitability affects stock price.